Changes of Trigonelline, Nicotinic Acid and Proline Content in Early Growth Stages of Trigonella foenum-graecum L. under Saline Condition - A Sahari Moghadam; A Mehrafarin; H Naghdi Badi (Institue of Medicinal Plants, ACECR, 2016)
Background: Some health-protecting secondary metabolites can be found at a higher concentration in the sprouts compared to other stages of plant growth. In addition, environmental stresses such as salt stress may be resulting in the increase or decrease of specific secondary metabolites in sprouts and plants. Objective: Evaluation the changes of trigonelline, nicotinic acid, and proline content of fenugreek sprouts under saline and non-saline condition in the different harvesting times. Methods: This experiment was conducted on the base of factorial experiment in completely randomized design with three replications. The treatments were included three levels of salinity (0, 75 and 150 mM of NaCl), and three harvesting times of sprouted fenugreek (4, 8 and 12 days after beginning the experiment). Results: In each level of salinity, the highest trigonelline content of sprouts was obtained on the fourth day, and its content was reduced on the eighth and twelfth days. The nicotinic acid amount under moderate (75 mM of NaCl), and severe (150 mM of NaCl) salinity was gradually reduced from the fourth up to twelfth days. Thus, the highest amount of nicotinic acid was observed on the fourth day, and its lowest was obtained on the twelfth day. The proline content of sprouted fenugreek was increased from the fourth up to twelfth day at different levels of salinity, so that the highest proline content of sprouts was observed on the twelfth day especially under 150 mM salinity. Conclusion: In general, the trigonelline and nicotinic acid content of sprouted fenugreek was reduced  from the fourth up to twelfth days, and the highest content of them was observed under 150 mM salinity on the  fourth day.